Zmiany warsztatu glottodydaktycznego na zajęciach z praktycznej nauki języka rosyjskiego na studiach filologicznych pierwszego stopnia - Buchowiecka-Fudała, Agata; Piekarska-Winkler, Dorota (Acta Polono-Ruthenica, 2018)
The purpose of this paper is to discuss the role of new findings on the mechanisms of learning and the development of information technology. The authors draw attention to the role of the teachers who feel inspired by the work and who want to modify the glottodidactics workshop, to stimulate curiosity of students, to develop their independence and create conditions for the development of formal education and the need for long-life-learning. Two concepts take on a fundamental importance: the dialogue of cultures and strong links between language and culture, expressed in principle - “language through culture, culture through language”.